Pengaruh Kualitas Produk, Pengalaman Pelanggan dan Kepuasan Pelanggan Terhadap Loyalitas Pelanggan (Studi Pada Pelanggan Marketplace Shopee Di Kota Bandung) - Meilani, Sri; Saputro, Arie Hendra (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
The growth of technology in Indonesia has had a significant impact on the transformation of the economic sector. This progress allows entrepreneurs to adapt quickly to market changes, by utilizing information technology as the main tool in their business operations. This study aims to determine the effect of product quality, customer experience, and customer satisfaction on customer loyalty (a study of Shopee customers in Bandung City). The research method used is a quantitative method with a descriptive verification approach. Sampling using a purposive sampling technique with a sample size of 100 people determined based on the criteria of Shopee users, customers who have shopped at Shopee, and domiciled in Bandung City. Measurement in the questionnaire uses a 5-point Likert scale. The data analysis technique in this study uses the SPSS v26 software application with the path analysis method. The results of this study indicate that product quality, customer experience, and customer satisfaction have a positive and significant effect on customer loyalty of Shopee customers in Bandung City simultaneously and contribute 0.483 or 48.3%. While the remaining 51.7% is influenced by other variables not discussed in this study.